Topological Analysis of Magnetically Induced Current Densities in Strong Magnetic Fields - Garner, Adam (2023)
Stagnation graphs provide a useful tool to analyse the main topological features of the, often complicated, vector field associated with magnetically induced currents. Previously these graphs have been constructed using response quantities appropriate for modest applied magnetic fields. An implementation capable of producing these graphs in arbitrarily strong magnetic fields is presented, using current-density-functional theory. This enables the study of how the topology of the current vector field changes with the strength and orientation of the applied magnetic field. Applications to CH4, C2H2 and C2H4 are presented. In each case we consider molecular geometries optimized in the presence of the magnetic field. The stagnation graphs reveal subtle changes to this vector field where the symmetry of the molecule remains constant. However, when the electronic state and symmetry of the corresponding equilibrium geometry changes with increasing field strength, the changes to the stagnation graph are extensive. The approach presented here will be helpful in interpreting changes in molecular structure and bonding in the strong-field regime.